2021
DOI: 10.3390/fi13070162
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Quality of Experience of Chinese College Students on Internet-Based Resources English Learning

Abstract: Since Internet-based resources provides various and practical forms of English learning materials, Internet-based resources English learning is a common way for the younger generation. However, not like adult learning, university students need stronger motivation to learn English from Internet-based resources. This study surveyed Chinese college students in Central China to reveal the relationship between cultural intelligence, hedonic motivation, English self-efficacy, online experience quality, and willingne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Additionally, using internet-based resources allows one to overcome limitations imposed by time, distance, and geography while still learning from native speakers. Moreover, young people frequently use smartphones for communication, entertainment, and education (Gao, 2021;Metruk, 2022).…”
Section: Impact Of the Internet On English Language Learningmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, using internet-based resources allows one to overcome limitations imposed by time, distance, and geography while still learning from native speakers. Moreover, young people frequently use smartphones for communication, entertainment, and education (Gao, 2021;Metruk, 2022).…”
Section: Impact Of the Internet On English Language Learningmentioning
confidence: 99%
“…For example, prior research has revealed that one of the key elements in learning English is English self-efficacy. Because students will be learning on their own, their abilities must be considered when talking about using online resources to learn English (Gao, 2021;Tao and Xu, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the rapid development of education informatization, online education has the advantages of convenience and wide dissemination of quality educational resources, and the commercialization platform of online education and its operation mode are developing rapidly and becoming more mature [1][2]. Online learning through educational platforms has become common for people to engage in learning activities.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, when compared to our country, China has indeed grown by leaps and bounds in recent decades, and they have developed in all aspects rapidly. Therefore, we need to learn English well and fully absorb the strengths of foreign countries [16][17][18]. However, in the process of self-learning English, there are often serious problems such as non-standard pronunciation, inaccurate reading of voice information, and inaccurate control of the degree of self-learning.…”
Section: Introductionmentioning
confidence: 99%